Proton Conductive Membranes from Covalently Cross-Linked Poly(Acrylate)/Silica Interpenetrating Networks - Zhyhailo, Mariia; Horechyy, Andriy; Meier-Haack, Jochen; Formanek, Petr; Malanin, Mikhail; Arnhold, Kerstin; Schneider, Konrad; Yevchuk, Iryna; Fery, Andreas (Macromolecular Materials and Engineering, 2021)
The preparation of hybrid proton conductive membranes that comprise of covalently linked interpenetrating polymer and inorganic networks is reported. The hybrid membranes are synthesized via simultaneous photo-initiated polymerization and sol–gel processing. The simultaneous processing permeates fabrication of the membranes that comprises covalently cross-linked polymeric and inorganic networks. The membranes are characterized by attenuated total reflectance-Fourier transform infrared spectroscopy, scaning electron microsopy, thermogravimetric analysis, differential scanning calorimetry, in order to confirm their chemical composition, structure, and morphology. An addition of 3-methacryloxypropyl trimethoxysilane into the sol–gel composition allows the formation of covalent linkages between polymeric and inorganic networks, which facilitates a uniform distribution of the molecular components across the fabricated membranes. The incorporation of the silica network leads to an increase in water retention and proton conductivity of hybrid membranes as compared to their purely polymeric analogues.
CRIS-Team Scopus Importer:2022-04-14
Keywords: 2-acrylamido-2-methylpropane sulfonic acid; 3-methacryloxypropyl trimethoxysilane; hybrid materials; proton conductive membranes; sol–gel process; ultraviolet-curing